Melatonin Suppresses Cyclic GMP-AMP Synthase-Stimulator of Interferon Genes Signaling and Delays the Development of Hearing Loss in the C57BL/6J Presbycusis Mouse Model. (1st May 2023) - Liu, Jinlan; Chen, Huiying; Lin, Xiaoyu; Zhu, Xiaoting; Huang, Jialin; Xu, Wenfeng; Tan, Ming; Su, Jiping
Highlights: Long-term supplementation of melatonin helps to delay the development of hearing loss in the C57BL/6J presbycusis mouse model. Melatonin reduces mtDNA release in the auditory pathway in C57BL/6J presbycusis mouse model. Melatonin inhibits cGAS-STING signaling pathway in the auditory pathway of C57BL/6J mice. Abstract: Melatonin supplementation has been shown to delay age-related hearing loss (ARHL) progression. Previously, melatonin was found to inhibit neuronal mitochondrial DNA (mtDNA) release, as well as inhibit cyclic GMP-AMP synthase (cGAS)-stimulator of interferon genes (STING) signaling, thereby delaying the onset of central nervous system diseases. Therefore, we hypothesized that melatonin may delay the progression of hearing loss in the C57BL/6J presbycusis mouse model by inhibiting cGAS-STING signaling in the auditory pathway. Oral melatonin at 10 mg/kg/d was administered to 3-month-old C57BL/6J mice until 12 months of age. The auditory brainstem response (ABR) threshold was used to assess their hearing ability. By real-time polymerase chain reaction and Western blot analysis, the levels of cytosolic mtDNA, cGAS/STING, and cytokines were examined in the mouse cochlea, inferior colliculus, and auditory cortex. We found that the 12-month-old control mice exhibited significant hearing loss, increased cytosolic mtDNA, increased expression of inflammatory factors TNF-α, IL-6, IFN-β, Cxcl10, and Ifit3, up-regulated cGAS and STING expression, and enhanced interferon regulatory factor 3 (IRF3) phosphorylation in the C57BL/6J mouse cochlea, inferior colliculus, and auditory cortex. Melatonin treatment significantly improved hearing, decreased cytosolic mtDNA, suppressed the expression of inflammatory cytokines TNF-α, IL-6, IFN-β, Ifit3, and Cxcl10, down-regulated cGAS and STING expression, and attenuated IRF3 phosphorylation in the C57BL/6J mouse cochlea, inferior colliculus, and auditory cortex. This study suggested that melatonin had a protective effect on auditory function in the C57BL/6J presbycusis mouse model, which may be mediated through reducing mtDNA release, inhibiting the cGAS-STING signaling pathway in the auditory pathway.